2016
DOI: 10.1161/hypertensionaha.115.06497
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Consumption and the Incidence of Hypertension in Three Prospective Cohort Studies

Abstract: Increased fruit and vegetable intake lowers blood pressure in short-term interventional studies. However, data on the association of long-term intake of fruits and vegetables with hypertension risk are scarce. We prospectively examined the independent association of whole fruit (excluding juices) and vegetable intake, as well as the change in consumption of whole fruits and vegetables, with incident hypertension in three large longitudinal cohort studies: Nurses’ Health Study (n=62,175), Nurses’ Health Study I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 35 publications
8
129
1
6
Order By: Relevance
“…A previous study reported that a quarter of all the food available is ultra‐processed food in households across 19 European countries and the household availability of ultra‐proceed food was positively associated to prevalence of obesity . High intake of plants food was only inversely associated with DBP at age 7y, in agreement with several studies that showed fruits and vegetable consumption had favorable effects on blood pressure . Nevertheless, we did not find any associations between plant based food and obesity or any other risk factors.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study reported that a quarter of all the food available is ultra‐processed food in households across 19 European countries and the household availability of ultra‐proceed food was positively associated to prevalence of obesity . High intake of plants food was only inversely associated with DBP at age 7y, in agreement with several studies that showed fruits and vegetable consumption had favorable effects on blood pressure . Nevertheless, we did not find any associations between plant based food and obesity or any other risk factors.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, further analysis of the role of specific vegetable and fruit species has been undertaken to identify potentially beneficial varieties and thus to allow consideration of the potential nutrient and phytochemical effects on health outcomes. A recent report of the beneficial effects of certain vegetables and fruits on the risks of developing hypertension is an excellent example of the approach required to advance our knowledge of the role of specific vegetable and fruit species on preventing disease …”
Section: Introductionmentioning
confidence: 99%
“…Borgi and colleagues analyzed 187,453 US adults for a mean follow-up time of 15.7 years. 24 They compared participants who consumed ≥ 4 servings/d of whole fruit to participants who consumed ≤ 4 servings/week of whole fruit, and found a multivariable adjusted HR of 0.92 (95% CI 0.87–0.97) for incident hypertension. When we analyzed 100% fruit juice and whole fruit dietary exposures using the same categories as Borgi et al, we found that whole fruit was associated with a similar, but non-significant decreased risk of hypertension (HR 0.94; 95% CI 0.83–1.05), and found that comparing the highest to lowest categories of 100% fruit juice consumption was associated with an increased risk of hypertension (HR 1.29; 95% CI 1.06–1.56), with a significant increasing trend across categories (P for trend = 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our outcome measure of incident hypertension was based on self-report, which has been used in other WHI analyses but has not been objectively validated. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation